Arab Republic of Egypt : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This paper analyzes that past growth was characterized by a suboptimal allocation of the factors of production and a lack of dynamism in the private sector. By identifying the main constraints to private sector-led growth and higher employment generation, it suggests policies to further shift Egypt's economic model toward increased private sector participation and integration into global value chains. To this end, reforms should aim at removing the distortions to the optimal allocation of resources in the economy and equip the labor force with the skills needed to benefit fully from future job opportunities. These reforms would also help better integrate women and youth into the job market. The authorities have embarked on a reform program to address these challenges and important steps have already been taken. Improved macrostability and a strong political commitment to reforms present an opportunity to further structural reforms that intensify private sector-led growth and job creation and strengthen trade integration.